Returns to Education in the Russian Federation : Some New Estimates - Patrinos, Harry; Parandekar, Suhas; Melianova, Ekaterina; Volgin, Artem (World Bank, Washington, DC, 2020)
This paper presents new estimates of the returns to education in the Russian Federation. Private returns to education are three times greater for higher education compared to vocational education, and the returns to education for females are higher than for males. Returns for females show an inverse U-shaped curve over the past two decades. Female education is a policy priority and there is a need to investigate the labor market relevance of vocational education. Higher education may have reached an expansion limit and it may be necessary to investigate options for increasing the productivity of schooling.